2023
DOI: 10.1039/d3cp01198d
|View full text |Cite
|
Sign up to set email alerts
|

Methanesulfonic acid and iodous acid nucleation: a novel mechanism for marine aerosols

Abstract: By seeding clouds, new particle formation (NPF) has a substantial impact on radiation balance, bio-geochemical cycles and global climate. Over oceans, both methanesulfonic acid (CH3S(O)2OH, MSA) and iodous acid (HIO2)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Iodine-containing compounds can be found in large concentrations in the atmosphere, especially in marine coastal environments but also in the Arctic and the Antarctic, due to large emissions from the ocean surface. , High concentrations of iodine-containing compounds have been shown to correlate with high particle concentrations and have been shown to lead to new particle formation in the Arctic and marine environments. ,,, The contribution of iodine-containing compounds to NPF has previously been studied with computational methods, but the exact contribution to NPF remains poorly understood . These studies have focused primarily on the formation of clusters with iodic acid (HIO 3 ) and iodous acid (HIO 2 ), either by themselves or in combination with other known nucleation precursors such as sulfuric acid, methanesulfonic acid, ammonia, and dimethylamine. , These studies show that iodic acid paired with either ammonia or dimethylamine generally forms very stable clusters, which could contribute significantly to particle formation.…”
Section: Introductionmentioning
confidence: 99%
“…Iodine-containing compounds can be found in large concentrations in the atmosphere, especially in marine coastal environments but also in the Arctic and the Antarctic, due to large emissions from the ocean surface. , High concentrations of iodine-containing compounds have been shown to correlate with high particle concentrations and have been shown to lead to new particle formation in the Arctic and marine environments. ,,, The contribution of iodine-containing compounds to NPF has previously been studied with computational methods, but the exact contribution to NPF remains poorly understood . These studies have focused primarily on the formation of clusters with iodic acid (HIO 3 ) and iodous acid (HIO 2 ), either by themselves or in combination with other known nucleation precursors such as sulfuric acid, methanesulfonic acid, ammonia, and dimethylamine. , These studies show that iodic acid paired with either ammonia or dimethylamine generally forms very stable clusters, which could contribute significantly to particle formation.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that diethylamine (DEA) has the highest EP, and sulfur oxoacids also have a high EP on the nucleation with HIO 3 as the partner . However, for the nucleation with HIO 2 as the partner, only the enhancement from HIO 3 and methanesulfonic acid (MSA) has been investigated. ,, More importantly, the EP of the same compounds on the nucleation with HIO 3 as the partner cannot simply be extrapolated to the nucleation with HIO 2 as the partner, due to the different properties and behaviors of HIO 3 and HIO 2 in neutral iodine oxoacid nucleation . Thus, evaluating the EP of abundant precursors on the nucleation with HIO 2 as the partner is warranted.…”
Section: Introductionmentioning
confidence: 99%